SENTENCE STRUCTURE AND PUNCTUATION IN ADVERTISEMENT SLOGANS - Aidas Borodinas; Jolanta Bareikienė (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose, 2021)
New businesses and products get into the market every day, and advertising is essential in the process of attracting customers. Advertisers analyse clients' behaviour and are trying to make their message as persuasive as possible. They try to use language which suggests that the product they advertise is of the highest quality. The purpose of the research is to find out what syntactic patterns and punctuation marks are most commonly applied in advertisement slogans. Advertisement slogans are mostly simple short sentences with a striking message. The main idea of an advertisement slogan is to reach the readers and affect them in a certain way by promoting the product of the advertising campaign. In order to achieve that the advertising creators use different sentence structures and punctuation marks. Two methods were applied - the analysis of theoretical references and the descriptive comparative linguistic analysis. The analysis of theoretical references gives a review of sentence structures and punctuation marks in advertisement slogans. The practical linguistic analysis was performed, 100 advertisement slogans were gathered on the internet from several different sources. Different cases of sentence structure and punctuation were defined and explained. Most frequently advertisement slogans are formed by using simple sentence structures. Declarative and imperative sentences were the most popular types of the sentence found in advertisement slogans. Declarative sentences are mostly formed by using a simple syntactic pattern. Imperative sentences are highly elliptical, the most common structure is a verb phrase. In advertisement slogans, punctuation marks can be neutral or not neutral. Neutral punctuation marks do not affect the emotional shade of the slogan. Not neutral punctuation marks not only punctuate advertisement slogans but create an emotional shade or help to emphasize the main idea of the slogan. Not in all cases do the creators of advertisement slogans obey the rules of grammar and they occasionally use punctuation as a stylistic device.